3D hierarchically porous zinc–nickel–cobalt oxide nanosheets grown on Ni foam as binder-free electrodes for electrochemical energy storage. Issue 47 (10th November 2015) - Chen, Huixin; Zhang, Qiaobao; Han, Xiang; Cai, Junjie; Liu, Meilin; Yang, Yong; Zhang, Kaili
Abstract : 3D hierarchically porous transition metal oxides, particularly those involving different metal ions of mixed valence states and constructed from interconnected nano-building blocks directly grown on conductive current collectors, are promising electrode candidates for energy storage devices such as Li-ion batteries and supercapacitors. Abstract : Three-dimensional (3D) hierarchically porous transition metal oxides, particularly those involving different metal ions of mixed valence states and constructed from interconnected nano-building blocks directly grown on conductive current collectors, are promising electrode candidates for energy storage devices such as Li-ion batteries (LIBs) and supercapacitors (SCs). This study reports a facile and scalable chemical bath deposition process combined with simple calcination for fabricating 3D hierarchically porous Zn–Ni–Co oxide (ZNCO) nanosheet arrays directly grown on Ni foam with robust adhesion. The resulting nanostructures are then evaluated as a binder-free electrode for LIBs and SCs. Given its unique architecture and compositional advantages, the electrode exhibits a reversible capacity of 1131 mA h g −1 after 50 cycles at a current density of 0.2 A g −1, an excellent long-term cycling stability at a high current density of 1 A g −1 for 1000 cycles, and a desirable rate capability when tested as an anode for LIBs. When used for SCs, the electrode demonstrates a high specific capacitance (1728 F g −1 at 1 A g −1 ), an outstanding rate capability (72% capacitance retention from 1 A g −1 to 50 A g −1 ), and an excellent cycling stability (capacitance of 1655 F g −1 after 5000 cycles at a current density of 20 A g −1 with 108.6% retention). Overall, the unique 3D hierarchically porous ZNCO nanosheets hold a great promise for constructing high-performance energy storage devices.